Berardinelli–Seip Congenital Lipodystrophy in a child: Classical phenotype with multisystem involvement from a resource-limited setting - Banik, Joy Datta; Hossain, Md Anowar; Mondal, Ershad; Banik, Sanjoy Ranjon (Journal of Association of Clinical Endocrinologist and Diabetologist of Bangladesh, 2026)
Berardinelli–Seip Congenital Lipodystrophy (BSCL) is a rare autosomal recessive disorder characterized by near-total absence of adipose tissue and severe metabolic derangements beginning in early life. We report a 10-year-old boy presenting with generalized lack of subcutaneous fat, acromegaloid features, hepatomegaly, insulin resistance, dyslipidemia, and hypertrophic cardiomyopathy. Characteristic clinical features supported by biochemical and radiological investigations established the diagnosis of BSCL. Genetic confirmation could not be performed due to limited resources. This case emphasizes the importance of careful phenotypic recognition for early diagnosis and timely management of BSCL, particularly in low-resource settings, to prevent long-term metabolic and cardiovascular complications. Early phenotypic recognition is critical for diagnosis of BSCL in the absence of genetic testing; severe insulin resistance and hepatic involvement are key diagnostic clues; comprehensive multisystem evaluation is essential in affected children. [J Assoc Clin Endocrinol Diabetol Bangladesh, January 2026; 5(1): 77-80]